Functionalized selenium nanoparticles enhance the anti-EV71 activity of oseltamivir in human astrocytoma cell model - Jiayu Zhong; Yu Xia; Liang Hua; Xiaomin Liu; Misi Xiao; Tiantian Xu; Bing Zhu; Hong Cao (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Enterovirus 71 (EV71) which commonly caused the hand-foot-mouth disease (HFMD) has become one of public health challenges worldwide. However, no effective vaccines or drugs for this disease has been developed. Thus, there is an urgent need to find a new strategy for treating the EV71 infection. Oseltamivir (OT) is an effective antiviral agent, but continuous use of oseltamivir leads to a diminished therapeutic effect in the clinic. In order to improve the antiviral activity of oseltamivir, oseltamivir was loaded onto surfaces of selenium nanoparticles (SeNPs) to fabricate a functionalized antiviral nanoparticles SeNPs@OT. The size of SeNPs@OT was tested by TEM and dynamic light scattering. The chemical structure and elemental composition of SeNPs@OT were analyzed by FT-IR and EDX, respectively. SeNPs@OT exhibited good stability and effective drug release in serum and PBS. SeNPs@OT efficiently entered into human astrocyte U251 cells (host cells) via clathrin-associated endocytosis and inhibited EV71 proliferation, which could protect EV71-infected U251 cells from apoptosis through mitochondrial pathway. Furthermore, SeNPs@OT inhibited EV71 activity probably by reducing the generation of reactive oxygen species in EV71-infected U251 cells. Interestingly, SeNPs obviously enhanced antiviral activity of oseltamivir in the anti-EV71 cell model. Taken together, SeNPs@OT is a promising antiviral drug candidate for EV71 infection.